Expecting pears from an elm tree : Franciscan missions on the Chiriguano frontier in the heart of South America, 1830-1949 - Langer, Erick Detlef (e-Duke books scholarly collection., 2009)
Franciscan missions were an influential aspect of frontier life in South America during the century after 1830, when newly established republics steadily imposed their jurisdiction over vast indigenous territories. Erick Langer explores the role of these missions among the Chiriguano people of the Bolivian Chaco.